Asociación entre nivel de conocimiento sobre alimentación saludable y hábitos alimentarios en estudiantes de medicina - Fernández Llajamango, Yelsin Erick (2021)
To determine the association between the level of knowledge about healthy eating and eating habits in medical students at the National University of Trujillo. MATERIALS AND METHODS: A cross-sectional study was conducted in which 263 students from the second to seventh year of the Medicine career of the National University of Trujillo were surveyed during the year 2021, using surveys. To determine the association between the variables, the Chi square statistical test was applied (CI: 95%). RESULTS: 84.0% (n=221) of students presented a medium level of knowledge about healthy eating; 10.3% (n=27) low level and 5.7% (n=15) high level. 97.7% (n=257) presented adequate eating habits and 2.3% (n=6) inadequate habits. The 27 students with a low level of knowledge presented adequate eating habits; Of the 221 students with a medium level of knowledge, 97.3% had adequate habits and only 2.7% had inadequate habits; the 15 with a high level of knowledge presented adequate eating habits (X²=1.17, p=0.5580; CI: 95%). CONCLUSION: There is no statistically significant association between the level of knowledge about healthy eating and eating habits in medical students at the National University of Trujillo.